Phosphorylation modification of tilapia skin gelatin hydrolysate and identification and characterization of calcium-binding peptides - Mei, Zhang; Jinlun, He; Hongyu, Pan; Liping, Sun; Yongliang, Zhuang (Process biochemistry (1991), 2023)
In present study, complex protease was utilized to prepare tilapia skin gelatin hydrolysate (TSGH), and the phosphorylation conditions of TSGH were optimized using calcium-binding capacity. The phosphorylation degree of TSGH under the optimal conditions was 0.55%. The calcium-binding capacities of TSGH and phosphorylated TSGH were 44.21 and 62.87 µg/mg, respectively. Phosphorylation remarkably improved the calcium-binding capacity of TSGH. Forty-four peptides and 14 phosphopeptides were identified in phosphorylated TSGH, and SGPAGPK and its phosphopeptide, (p)SGPAGPK, were screened. The calcium chelates of SGPAGPK and (p)SGPAGPK were examined using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and mass spectrometry (MS). Phosphorylation of SGPAGPK effectively increased its calcium-binding capacity. SEM results indicated that SGPAGPK-Ca and (p)SGPAGPK-Ca were formed as new compounds. FTIR and MS results indicated that the carboxyl and phosphate groups of Ser and the amino group of Lys may be the calcium chelation sites. [Display omitted] •Tilapia skin gelatin hydrolysate (TSGH) was obtained by complex protease.•Phosphorylation conditions of TSGH were optimized by calcium-binding capacity.•Phosphorylation remarkably improved the calcium-binding capacity of TSGH.•Key peptides and phosphopeptides were identified in phosphorylated TSGH.•Structural characteristics of SGPAGPK-Ca and (p)SGPAGPK-Ca were examined.